2006
DOI: 10.1111/j.1365-2591.2006.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of different gutta‐percha brands during the filling of simulated lateral canals

Abstract: The brand of gutta-percha cone had an influence on the length of filling within lateral canals. This may be a reflection of the chemical formulation of the gutta-percha points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 15 publications
(42 reference statements)
2
46
0
11
Order By: Relevance
“…29 Greater flow has been reported for cones containing higher percentages of gutta-percha in their formulation. 14 The mean of the percentage by weight of gutta-percha points in Odous cones is 18.8, and that of Dentsply is 0.04 is 15.7. 30 In the present study, Odous gutta-percha had better results than Dentsply gutta-percha in the coronal third, which suggests the presence of a greater percentage of gutta-percha in its formulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Greater flow has been reported for cones containing higher percentages of gutta-percha in their formulation. 14 The mean of the percentage by weight of gutta-percha points in Odous cones is 18.8, and that of Dentsply is 0.04 is 15.7. 30 In the present study, Odous gutta-percha had better results than Dentsply gutta-percha in the coronal third, which suggests the presence of a greater percentage of gutta-percha in its formulation.…”
Section: Discussionmentioning
confidence: 99%
“…5,15,19 Gutta-percha cones are composed of barium sulfate, zinc oxide, wax, resin and gutta-percha, but the proportions of these components are not constant. 14 The percentage of inorganic components in the formulation of commercially available gutta-percha may affect its thermal properties. 29 Greater flow has been reported for cones containing higher percentages of gutta-percha in their formulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,19 These methods rely on the thermoplastic properties of gutta-percha, which may vary among the different types of commercially available gutta-percha. 8,19 In this study, artificial lateral root canals were prepared using a bur with a diameter of 0.3 mm. The aim of this study was to compare the plasticity of solid root canal filling materials (gutta-percha and Resilon) used without an endodontic sealer by evaluating the ability of these materials to fill simulated lateral canals.…”
Section: Discussionmentioning
confidence: 99%
“…17 Although several endodontic techniques have been evaluated with respect to their ability to adequately fill the root canal and its irregularities, 9,11,12 few studies have focused on the thermoplasticity of different brands of guttapercha and Resilon when using thermoplastic techniques. 8,19,20 Resilon (Resilon Research LLC, Madison, USA), a synthetic polymer-based material, has been proposed as an alternative to gutta-percha. 7 The thermoplastic properties of Resilon were studied by Miner et al, 10 who demonstrated that Resilon and gutta-percha have similar melting points of approximately 60 °C.…”
Section: Introductionmentioning
confidence: 99%